(untitled) (Impact: Journal of Transformation, 2022)
Several studies indicate that social enterprises have contributed tremendously to social transformation in different ways. The impact of social entrepreneurship in Africa links correctly to Ubuntuism, which emphasizes a culture of interdependence and reciprocity over individualism and self-interest, to a cultural belief in community/societal interest above individual gain. This paper sought to investigate the influence of entrepreneurial culture on social transformation in Kiambu County, Kenya. The study used a descriptive survey design with a sample size of 322 social enterprises from a target population of 1944 social enterprises spread over 12 sub-counties of Kiambu. The study used several sampling techniques. First, the study used purposive sampling to select Kiambu County; secondly, the study used stratified sampling technique to stratify the social enterprises according to the 12 sub-counties belonging to Kiambu County. Finally, the study used simple random sampling to pick respondents from each strata for the study. From the findings, entrepreneurial culture by social enterprises was found to predict social transformation as indicated by F(3, 281) = 55.990, p<.05. Likewise, the results from the p-values shows there is a positive significant correlation between entrepreneurial culture and social transformation by social enterprises (r = 0.448, p = 0.000) in Kiambu County. The study concludes that entrepreneurial culture, when applied properly, has a positive effect on social transformation by social enterprises. These findings are useful to different stakeholders; most importantly, the national and county governments and the academia in Kenya. Future studies can extend the sample size and diversify the variables for better understanding of the field of social enterprises in social transformation.